Assessing the Risk of Groundwater Contamination from Drinking Water Well Condition - Hickman, John S.; Herbel, Kevin L.; Rogers, Danny H.; Powell, Morgan G. (My University, 1998)
A step by step through drinking water well condition and management practices to help protect groundwater that supplies drinking water.
EP42_1998-08
Keywords: EP42; Environment and Natural Resources; Equipment and Structures; Health and Safety; EP